Peran Pendidikan Orang Tua dalam Pengambilan Keputusan Terhadap Program Mengaji Anak di Komplek Perumahan Pagar Dewa Kota Bengkulu - Azi Wahyuda; Diana Lorenza; Novita Rahmayanti; Asniti Karni (Yayasan Darussalam Bengkulu, 2025)
This study aims to: 1) to describe the role of parents in 2) to describe the supporting and inhibiting factors of parents in teaching the Qur'an to children (7-15 years old) in Pagar Dewa Housing Complex RT.45 RW.01 Bengkulu City. The method in this research is included in the type of field research and in terms of the type of data collected is included in the qualitative approach research. The results of the research answer the formulation of the problem, among others, it is known that: 1) Most parents in Pagar Dewa housing RT.45 RW.01 Bengkulu City have played a role in providing guidance, supervision, encouragement to children in reading the Qur'an, and modeling good habits, providing punishment and rewards, and instilling education, especially religious education with Islamic concepts, fulfilling children's needs optimally, although only a few families guide their children directly without entrusting their children to Qur'anic education institutions such as TPA or TPQ; 2) Supporting factors are the existence of Qur'anic educational institutions such as TPA or TPQ while the inhibiting factors of parents in teaching the Qur'an to children are the limited knowledge of parents and parents' busyness, non-agamist environment or association.